Philosophy and history of education : diverse perspectives on their value and relationship - Errante, Antoinette; Blount, Jackie M., 1959-; Kimball, Bruce A., 1951- (Rowman & Littlefield, 2017)
Philosophy and History of Education examines the complex relationship between the study of philosophy and history, and the value of these related studies for improving educational knowledge, policy, and practice.